2014
DOI: 10.5120/16673-6677
|View full text |Cite
|
Sign up to set email alerts
|

Application of Factor Analysis to k-means Clustering Algorithm on Transportation Data

Abstract: Factor Analysis is a very useful linear algebra technique used for dimensionality reduction. It is also used for data compression and visualization of high dimensional datasets. This technique tries to identify from among a large set of variables, a reduced set of components which summarizes the original data. This is done by identifying groups of variables which have a strong inter correlation. The original variables are transformed into a smaller set of components which have a strong linear correlation. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Other compelling applications of cluster analysis include a study of dietary habits in Canada [34] and Hungary [35], and household appliances in Germany [36], but their scope is limited to particular consumption domains rather than being applicable to the environmental impact of lifestyles as a whole. Combining these two methods of factor analysis and cluster analysis was an approach taken by a previous comparative study, which concluded that using the results of exploratory factor analysis as inputs for cluster analysis improves the quality of clusters [37]. Drawing on this conclusion, the present study thus combines cluster analysis and exploratory factor analysis to examine variations in carbon footprints within a country based on the underlying lifestyle factors.…”
mentioning
confidence: 91%
“…Other compelling applications of cluster analysis include a study of dietary habits in Canada [34] and Hungary [35], and household appliances in Germany [36], but their scope is limited to particular consumption domains rather than being applicable to the environmental impact of lifestyles as a whole. Combining these two methods of factor analysis and cluster analysis was an approach taken by a previous comparative study, which concluded that using the results of exploratory factor analysis as inputs for cluster analysis improves the quality of clusters [37]. Drawing on this conclusion, the present study thus combines cluster analysis and exploratory factor analysis to examine variations in carbon footprints within a country based on the underlying lifestyle factors.…”
mentioning
confidence: 91%
“…For clarity of reference, factor categories and clusters are directly presented in the following section. Since several studies found benefits in combining cluster and factor analyses (Anand et al. , 2014; Gorman and Primavera, 1983; Visbal-Cadavid et al.…”
Section: Methodsmentioning
confidence: 99%
“…For clarity of reference, factor categories and clusters are directly presented in the following section. Since several studies found benefits in combining cluster and factor analyses (Anand et al, 2014;Gorman and Primavera, 1983;Visbal-Cadavid et al, 2020), the output of these two analyses was studied together in this paper to understand the integrated dynamics of macroeconomic and policy measures within country groups. Differences across years and clusters were assessed, and policy influences and variations in the resulting cluster "rankings" were verified.…”
Section: Methodsmentioning
confidence: 99%
“…The benefit of applying this technique is that when the data is reoriented, the first few dimensions obtained show maximum variance, i.e. they give the maximum amount of information as reflected by their respective eigenvalues wherein each principal component resembles a linear combination of the original data (Anand et al , 2014). Thus, the fundamental principle for applying PCA is to help visualize complex data sets by eliminating unnecessary dimensions which do not add much value to the data that is present.…”
Section: Methodsmentioning
confidence: 99%